Glioma-associated radiation retinopathy treated successfully with aflibercept - Karagiannis D; Kontomichos L; Georgalas I; Peponis V; Antoniou E; Parikakis E (Dove Medical Press, 2019)
D Karagiannis,1 L Kontomichos,1 I Georgalas,2 V Peponis,1 E Antoniou,3 E Parikakis11Second Department of Ophthalmology, Opthalmiatreion Eye Hospital of Athens, Athens, Greece; 2First Department of Ophthalmology, National and Kapodistrian University of Athens, Athens, Greece; 3Moorfields Eye Hospital, London, UKAbstract: Radiation retinopathy is a chronic, progressive retinal microangiopathy which can occur with variable latency after retina exposure to ionizing radiation used for cancer treatment. It can occur secondary to treatment of nasopharyngeal tumors, as well as intraocular tumors, such as uveal melanoma and retinoblastoma. Several treatment modalities have been reported including intravitreal corticosteroids, intravitreal anti-VEGFs and argon laser photocoagulation. Our purpose is to present a case report of bilateral radiation retinopathy with macular edema in one eye that was revealed 6 years after glioma therapy and treated successfully by using monotherapy of aflibercept. A 59-year-old male patient presented with gradually deteriorating visual acuity in his left eye for the past 12 months. Best corrected visual acuity in his right eye was 20/25 and in his left eye 20/100. Fundoscopy and fluorescein angiography revealed severe non-proliferative retinopathy in his right eye and proliferative retinopathy in his left eye with macular edema. Following complete work-up and due to his past medical history, he was diagnosed with radiation retinopathy. The patient received 6 intravitreal injections of aflibercept in a period of 9 months in order to treat macular edema and radiation retinopathy. According to the literature, there is minimal experience using aflibercept monotherapy to successfully treat macular edema due to radiation retinopathy. In addition, radiotherapy for glioma is a rather rare cause of radiation retinopathy compared to other more common causes, such as nasopharyngeal tumors, meningiomas, and uveal melanomas.Keywords: aflibercept, macular edema, glioma, radiation retinopathy